Financial Leverage Terhadap Earning Per Share Perusahaan Makanan dan Minuman di Bursa Efek Indonesia - Dian Anugrah Sanusi (Universitas Sam Ratulangi, 2020)
This research aims to determine the significant influence between Financial Leverage on Earning Per Share (EPS) on food and beverage companies listed on the Indonesia Stock Exchange. The variables in this research are Financial Leverage (X) and Earning Per Share (Y), with a unit of measurement of percentage (%). The population is all food and beverage companies listed on the Indonesia Stock Exchange, which sampled as many as 5 companies over five years, namely in 2009-2013 by purposive sampling. Data collected is processed using the ratio of debt to equity ratio and earning per share. To test the hypothesis used simple linear regression analysis techniques, correlation, and t-test. Based on the results of the correlation shows a low relationship, this is in accordance with the interpretation guidelines while the coefficient of determination is the influence of financial leverage on earning per share is 7.4%, while the remaining 92.6% is determined by other factors not examined by researchers. For the significance test, there is no effect of financial leverage on earnings per share in food and beverage companies listed on the Indonesia stock exchange.